Autotitrating Bilevel Positive Airway Pressure in Large Vessel Steno-Occlusive Stroke Patients With Suspected Sleep Apnea: A Multicenter Randomized Controlled Study - Barlinn, Kristian; Jakubicek, Stanislava; Siepmann, Timo; Chernyshev, Oleg Y.; Pallesen, Lars-Peder; Wienecke, Miriam; Hermann, Wiebke; Graehlert, Xina; Alexandrov, Anne W.; Vosko, Milan; Puetz, Volker; Reichmann, Heinz; et al. (Frontiers in Neurology, 2021)
Background: We hypothesized that autotitrating bilevel positive airway pressure (auto-BPAP) favorably affects short-term clinical outcomes in hyperacute ischemic stroke. Methods: In a multicenter, randomized, controlled trial patients with large vessel steno-occlusive stroke and clinically suspected sleep apnea were allocated to auto-BPAP or standard stroke care alone. Auto-BPAP was initiated within 24 h from stroke onset and performed over 48 h during diurnal and nocturnal sleep. Sleep apnea was assessed using cardiorespiratory polygraphy. Primary endpoint was early neurological improvement on National Institutes of Health Stroke Scale (NIHSS) score at 72 h. Safety and tolerability of BPAP, functional independence [modified Rankin Scale (mRS) 0–2], stroke recurrence, and mortality at 90 days were assessed. Results: Due to low recruitment, the trial was prematurely stopped after 24 patients had been randomized (auto-BPAP, n = 14; control, n = 10): median baseline NIHSS 13 (5.5–18), 88% large vessel occlusion, and 12% large vessel stenosis. Polygraphy confirmed sleep apnea in 64% of auto-BPAP and 88% of control patients (p = 0.34). Adherence to auto-BPAP was achieved by 9 of the 14 (64%) patients. Between auto-BPAP and control patients, no differences were observed in early neurological improvement (median NIHSS change: −2.0, IQR = 7 points vs. −0.5, IQR = 3 points), 90 days functional independence (21 vs. 30%, p = 0.67), stroke recurrence (0 vs. 20%, p = 0.16), and death (14 vs. 20%, p = 1.0). No safety concerns were identified. Conclusions: In this prematurely terminated trial, auto-BPAP was safe but did not show an effect on short-term clinical outcomes in selected ischemic stroke patients. Its tolerability, however, may be limited in hyperacute stroke care and needs to be improved before larger trials are conducted. Clinical Trial Registration:ClinicalTrials.gov, identifier: NCT01812993.